2017
DOI: 10.1038/s41598-017-06036-y
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density, blood telomere length and lipid peroxidation

Abstract: Extensive mammographic density is a strong risk factor for breast cancer, but may also be an indicator of biological age. In this study we examined whether mammographic density is related to blood telomere length, a potential marker of susceptibility to age-related disease. We measured mammographic density by a computer assisted method and blood telomere length using a validated PCR method. Urinary malondialdehyde (MDA), a marker of lipid peroxidation, was measured in 24 hour urine collections. In the 342 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Patients over 50 years at diagnosis displayed reduced levels of hydroperoxides when compared to younger patients. Although no studies reporting the lipid peroxidation status in breast cancer women considering their age at diagnosis were found, our findings follow recent evidence that reported a positive relationship between telomere length and urinary levels of lipid peroxidation metabolites in healthy women [ 24 ]. Further, results presented here indicate that the presence of lymph nodal metastasis seems to nullify the differences observed concerning the age of patients.…”
Section: Discussionsupporting
confidence: 89%
“…Patients over 50 years at diagnosis displayed reduced levels of hydroperoxides when compared to younger patients. Although no studies reporting the lipid peroxidation status in breast cancer women considering their age at diagnosis were found, our findings follow recent evidence that reported a positive relationship between telomere length and urinary levels of lipid peroxidation metabolites in healthy women [ 24 ]. Further, results presented here indicate that the presence of lymph nodal metastasis seems to nullify the differences observed concerning the age of patients.…”
Section: Discussionsupporting
confidence: 89%
“…All studies, included in the final review, that met eligibility criteria were published between the years 2011–2022. Eight of these studies were conducted in the United States [ 10 , 58 60 , 65 67 , 69 ], two in Canada [ 63 , 68 ], two in Central America [ 57 , 64 ] one in the Philippines [ 61 ] and one in Israel [ 62 ]. Of the studies assessing parity and TL, three utilized a longitudinal research design [ 10 , 57 , 61 ], seven reported data from a cross-sectional study design [ 58 60 , 63 66 ] and one study utilized a case control retrospective study design [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight of these studies were conducted in the United States [ 10 , 58 60 , 65 67 , 69 ], two in Canada [ 63 , 68 ], two in Central America [ 57 , 64 ] one in the Philippines [ 61 ] and one in Israel [ 62 ]. Of the studies assessing parity and TL, three utilized a longitudinal research design [ 10 , 57 , 61 ], seven reported data from a cross-sectional study design [ 58 60 , 63 66 ] and one study utilized a case control retrospective study design [ 62 ]. All studies assessing TL dynamics throughout pregnancy utilized a longitudinal research design [ 10 , 67 – 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations